Knowledge, attitude and practice on antimicrobial use and antimicrobial resistance among competent persons in the community pharmacies in Bhutan - Tenzin, Jigme; Tshomo, Kinley Penjor; Wangda, Sonam; Gyeltshen, Wangdi; Tshering, Gyem (Frontiers in Public Health, 2023)
Introduction Since the discovery, antimicrobials have been used to treat variety of infections both in humans and animals caused by microbes. However, with the increasing use, microbes developed resistance to the antimicrobials and many of the antimicrobials became ineffective against certain microbes. Many factors are reported to contribute to the resistance of microbes to antimicrobials. One contributing factor is the misuse and overuse of antibiotics which mainly occur due to the lack of knowledge, careless attitudes, and incorrect practices about use of antibiotics. Methods This cross-sectional survey study was conducted among the competent persons (CP) in the community pharmacies in Bhutan, with the aim to assess their knowledge, attitude and practice (KAP) on antimicrobial use (AMU) and antimicrobial resistance (AMR). Results Results from the survey revealed that the competent persons had good level of knowledge about antimicrobial use and antimicrobial resistance. They also had favourable attitude towards antimicrobial resistance and rational use of antimicrobials. Their knowledge and attitude had led to good practices while dispensing antimicrobials from their pharmacies. However, almost all of them had never had any opportunity to take part in activities related to antimicrobial use and antimicrobial resistance that were organized by the public sector. Many of them did not even hear or know about the existence of the policies on use of antimicrobials or on curbing antimicrobial resistance in the country. Conclusion Involvement of the community pharmacies through trainings and participations in policy making processes is seen as a vital mechanism that can eventually help achieve the goals in the national drive towards reducing antimicrobial resistance.